TUMBUHAN LIAR YANG DIMANFAATKAN SEBAGAI OBAT PADA SUKU KENYAH DI DESA LONG NORAN, KALIMANTAN TIMUR - Rita Diana; Paulus Matius; Teffani Angela (Universitas Tanjungpura, 2023)
Wild plants are trees or other woody plants that have the potential to be a valuable natural resource for the people of the world. Wild plants with medical capabilities are plants that contain compounds that can be used to treat disease in the human body or organs, as was the case with the Dayak Kenyah Long Noran village in Telen subdistrict, East Kutai Regency, East Kalimantan. This study was carried out in the village of Long Noran, subdistrict Telen, East Kalimantan, with the goal of discovering the wild plants utilised by the people of Long Noran village, how they were processed, and the plant parts used. The purposive sampling approach was employed, with 20 female and 20 male respondents. Then I spent a month interviewing the villagers of Long Noran village. According to the interview results, the people of Long Noran village use 42 plants. According to the study's findings, it is made up of six different species of plants: perdu, herbs, liana, trees, palms, and nails. Shrubs (26%), herbaceous (29%), and the final form of plant, with as much as 2%, are the most used types of plants. The leaf is the most utilised portion of the plant (59%), while the skins and flowers are the least commonly used. Stems and bulbs might contribute up to 2%. The management of wild plants as chewed, boiled, crushed, thickened, and smoked, and the processing method that is frequently employed is boiled by 70% and at least smoked by 4%. Wild flora can be found in the settlement of Long Noran's Fields, former fields, house fields, wetlands, riverbanks, main woods, and plantations. This wild plant is most usually found in the house (27% of the time) and at least in marshes (2% of the time). Meanwhile, Aka Penawar has the highest usability index at 2.66, while Kangkung Bala has the lowest at 1.37.